Inter-Turn Short Circuits in Stator Winding of Permanent Magnet Synchronous Generator Dedicated for Small Hydroelectric Power Plants - Adam Gozdowiak; Maciej Antal (Energies)
This article presents the simulation results of inter-turn short circuits in the stator winding of a permanent magnet synchronous generator (PMSG) dedicated for small hydroelectric power plants. During the calculations, a field–circuit model is used via ANSYS software. The simulations were performed for both a fault-free generator and faulty generator with various degrees of short-circuited turns under various operating conditions. The degree of stator winding damage is modeled by changing the number of shorted turns in one phase. The studied generator has a two-layer stator winding made of winding wire. In addition, it is made of three parallel branches. In this way, a more difficult-to-detect condition is simulated. We analyzed the influences of short-circuit fault on the magnetic field and their impact on generator behavior. The analysis of the obtained results indicates the possibility of using the measurement of the stator current histogram, higher-order harmonics of the stator current, back electromotive force (back EMF), phase current growth, and power factor fluctuations for early detection of an inter-turn short circuit.